Disrupting Notch signaling related HES1 in myeloid cells reinvigorates antitumor T cell responses - Myung Sup Kim; Hyeokgu Kang; Jung-Hwan Baek; Moon-Gyu Cho; Eun Joo Chung; Seok-Jun Kim; Joon-Yong Chung; Kyung-Hee Chun (Experimental Hematology & Oncology)
Abstract Background Tumor-associated macrophages (TAMs) are immunosuppressive cells within the tumor microenvironment (TME) that hinder anti-tumor immunity. Notch signaling is a pathway crucial for TAM differentiation and function. Here, we investigate the role of HES1, a downstream target of Notch signaling, in TAM-mediated immunosuppression and explore its potential as a target for cancer immunotherapy. Methods In this work, we constructed conditional Hes1 knockout mice to selectively delete Hes1 in TAMs. We further analyzed the TME composition, T cell infiltration and activation, and anti-tumor effects in these mice, both alone and in combination with PD-1 checkpoint blockade. Results Our study showed that expression levels of Notch target Hes1 were increase in TAMs and mice with conditional knockout of Hes1 gene in TAMs exhibited decreased tumor growth, with increased infiltration and activation of cytotoxic T cells in tumors. Expression of tumor promoting factors was critically altered in Hes1-conditional KO TAMs, leading to the improved tumor microenvironment. Notably, arginase-1 expression was decreased in Hes1-conditional KO mice. Arg1 is known to deplete arginine and deactivate T cells in the TME. Administration of anti-PD-1 monoclonal antibody inhibited tumor growth to a greater extent in Hes1-conditional KO mice than in WT mice. Conclusions We identified a pivotal role for the Notch signaling pathway in shaping TAM function, suggesting that T-cell dysfunction in the TME is caused when the Notch target, HES1, in TAMs is upregulated by tumor-associated factors (TAFs), which, in turn, increases the expression of arginase-1. Targeting HES1 in TAMs appears to be a promising strategy for cancer immunotherapy.